ANALYSIS OF PHONOLOGICAL ERRORS IN TODDLERS: CASE STUDY CHILDREN AGES 2-2.5 YEARS - Endang Sri Andayani (GoAcademica Research dan Publishing, 2021)
We can be sure that humans speak whatever they do, whether they drive, play, work or make friends. People live in the linguistic world. Everybody may interact with their families, colleagues, teachers or even strangers in human language. The study took place in Bandung in May 2021. The tool used in this research is a qualitative method with an application to case studies. In kids aged 2-2 years six months, the data source has been collected from an FA child using qualitative methods. The design of the study was longitudinal. The FA has obtained research data through observations, notes and interviews between the FA and its parents. The results of this article indicate that the phoneme [a], I [u], [o], [alternative], [alternative], [alternatively] and [alternative] is mastered by TPM. At the age of 2 years and one month, he mastered vocal phonemes. The first vowels he learned were the [a], I [u], I then the front vowels I [e], [т], [o], [first], [middle vowel] [first], [a]. Vowels not diphenic in nature were, for instance [au], [ai] and [ue], also mastered at the age of 2 years and three months. However, the initial [au] and [ai] diphthongs were not perfected until they were two years old and six months old. At the same time, there is a good deal of mastery in the consonants [p], [b], [t], [t], [h], [j], [n], [p], [p], [l], [f], and [y]. The [t], [s], [c], [j] and [alias] consonants have been found but still fluctuate in other sounds. The tone of the Velar [g], [k] inhibition is not properly pronounced. The sound [k] can only be regulated if at the centre and the end of a phrase. The sound [f] and [v] and the sound [r] are not yet new and have not yet been regulated. The TPM executes the phones that it has not managed to pronounce, such as phonemes [f], [v], [z] and [x], in a replaceable pattern.